STRATEGI PENCEGAHAN TINDAK PIDANA KORUPSI PADA PEMILU DAN PILKADA SERENTAK 2024 - Dairani Dairani (HUKMY : Jurnal Hukum, 2023)
Indonesia is a constitutional state with a democratic government where all citizens get equal rights in a democratic party with the principle of fairness and justice. However, in implementation of the election there were many violations, for example money politics, power and influence of power. This study aims to find out what the right strategy is to deal with corruption in general elections and local elections in 2024. Normative juridical research methods are used to investigate, find, and describe quality in the upcoming 2024 election. There were many violations in the 2019 election and found 6,649 offenders who committed corruption. Based on ICW data, there were 579 corruption cases that have been prosecuted in Indonesia throughout 2022. There are strategies and steps in eradicating corruption in elections in Indonesia, namely with a sanction and criminal system that has been regulated in Law No. 7 of 2017 maximize criminal sanctions for money politics. In an effort to prevent money politics from occurring in the upcoming 2024 parliamentary elections, this research offers several aspects of law enforcement and the constitution which include limits on campaign funds for both candidates and political parties as well as a prohibition on former corruption convicts from running again. The second side focuses on 3 aspects, namely election organizers who are independent and consistent, political parties that do not provide recommendations for candidates who do not have integrity and capacity and finally voters who have integrity without being tempted by transactional politics which makes election.